2021
DOI: 10.1097/brs.0000000000004015
|View full text |Cite
|
Sign up to set email alerts
|

Dapsone Prevents Allodynia and Hyperalgesia and Decreased Oxidative Stress After Spinal Cord Injury in Rats

Abstract: Study Design. Prospective longitudinal experimental study. Objective. We evaluate the effect of dapsone on tactile allodynia and mechanical hyperalgesia and to determine its antioxidant effect in a spinal cord injury (SC) model in rats. Summary of Background Data. Neuropathic pain (NP) as result of traumatic spinal cord injury is a deleterious medical condition with temporal or permanent time-course. Painful stimuli trigger a cascade of events that activate the N-methyl-Daspartate (NMDA) receptor, inducing an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Dapsone has demonstrated the ability to attenuate the development of striatal necrosis [ 148 ] and the depletion of gamma-aminobutyric acid levels [ 149 ] after the injection of quinolinic acid, a neurotoxic NMDA receptor agonist. Dapsone might prevent excessive lipid peroxidation [ 148 ] or glutamate agonism [ 149 ], which was corroborated by a spinal cord injury (SCI) murine model in which dapsone appeared to antagonize lipid peroxidase and normalize glutathione concentrations [ 150 ]. Notably, tactile allodynia and mechanical hyperalgesia were similarly improved with either early (3 hours post-injury) or delayed administration (15 days post-injury) of dapsone [ 150 ].…”
Section: Main Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Dapsone has demonstrated the ability to attenuate the development of striatal necrosis [ 148 ] and the depletion of gamma-aminobutyric acid levels [ 149 ] after the injection of quinolinic acid, a neurotoxic NMDA receptor agonist. Dapsone might prevent excessive lipid peroxidation [ 148 ] or glutamate agonism [ 149 ], which was corroborated by a spinal cord injury (SCI) murine model in which dapsone appeared to antagonize lipid peroxidase and normalize glutathione concentrations [ 150 ]. Notably, tactile allodynia and mechanical hyperalgesia were similarly improved with either early (3 hours post-injury) or delayed administration (15 days post-injury) of dapsone [ 150 ].…”
Section: Main Bodymentioning
confidence: 99%
“…Dapsone might prevent excessive lipid peroxidation [ 148 ] or glutamate agonism [ 149 ], which was corroborated by a spinal cord injury (SCI) murine model in which dapsone appeared to antagonize lipid peroxidase and normalize glutathione concentrations [ 150 ]. Notably, tactile allodynia and mechanical hyperalgesia were similarly improved with either early (3 hours post-injury) or delayed administration (15 days post-injury) of dapsone [ 150 ]. Other SCI murine models have shown that dapsone can improve neurological function by reducing cell apoptosis [ 151 ] and inhibiting myeloperoxidase [ 152 ], limiting the extent of neurological tissue damage.…”
Section: Main Bodymentioning
confidence: 99%